The US-China Trade War in Macroeconomic Studies of the Indonesian Sharia Stock Index - Muhammad Adi Adrian; Mohammad Rofiuddin (Shirkah: Journal of Economics and Business, 2023)
A number of studies have been the witness of pros and cons about whether the US-China trade war affected the world’s macroeconomics. This study aims to analyze the effect of macroeconomic variables on the Indonesian Sharia Stock Index (ISSI) during the trade war period between the United States and China. The research’s assumption is delved from the occurrence of a trade war between two countries with the largest economic valuations in the world can disrupt the world economy including investment. The urgency of this research is to measure the impact of the trade war on the Indonesian sharia stock index which is one of the factors of economic growth. The analytical method used in this study is the Vector Error Correction Model (VECM) to examine the long-term and short-term impacts. The results of this study indicate that in the short term the BI Rate, FED Rate, USD Exchange Rate, CNY Exchange Rate, World Gold Price, World Oil Price, Exports, and Imports have no effect on the Indonesian Sharia Stock Index (ISSI). The long-term results show that the BI Rate, CNY Rate, World Gold Price, World Oil Price, and Imports have a negative effect on the Indonesian Sharia Stock Index (ISSI), while the FED Rate, USD Rate, and Exports have a positive effect on the Indonesian Sharia Stock Index (ISSI). Based on these results the government is expected to tighten fiscal and monetary policies so that in the future if something similar happens, the Indonesian Sharia Stock Index (ISSI) remains on the right track.